2021
DOI: 10.1371/journal.pone.0248485
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA gene amplicon-based metagenomic analysis of bacterial communities in the rhizospheres of selected mangrove species from Mida Creek and Gazi Bay, Kenya

Abstract: Prokaryotic communities play key roles in biogeochemical transformation and cycling of nutrients in the productive mangrove ecosystem. In this study, the vertical distribution of rhizosphere bacteria was evaluated by profiling the bacterial diversity and community structure in the rhizospheres of four mangrove species (Sonneratia alba, Rhizophora mucronata, Ceriops tagal and Avicennia marina) from Mida Creek and Gazi Bay, Kenya, using DNA-metabarcoding. Alpha diversity was not significantly different between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 68 publications
3
17
0
Order By: Relevance
“…These results were in agreement with findings of Xie et al [ 3 ], who suggested that organic amendments with abundant nutrients not only directly affect soil carbon and nitrogen cycling processes, but also had an enormous impact on microbial species and activities, which in turn affected the C- and N-relevant transformations. For instance, significantly positive relationships among nutrients and pronounced core families of Hyphomicrobiaceae , Cytophagaceae , Pirellulaceae , Microbacteriaceae , and Phyllobacteriaceae were observed in our study ( Figure 3 A and Figure 5 ), suggesting the enhanced carbon and nitrogen biogeochemical processes in soils after sewage sludge usage, as these families have been widely reported to be capable of participating in relevant functions [ 109 , 110 , 111 , 112 ]. Together, these outcomes suggested that sewage sludge significantly improved the diversity of the bacterial community and functionality mainly by ameliorating microhabitats in coastal mudflat soil, which harbored alleviated saline–alkali conditions and promoted available nutrients.…”
Section: Discussionsupporting
confidence: 58%
“…These results were in agreement with findings of Xie et al [ 3 ], who suggested that organic amendments with abundant nutrients not only directly affect soil carbon and nitrogen cycling processes, but also had an enormous impact on microbial species and activities, which in turn affected the C- and N-relevant transformations. For instance, significantly positive relationships among nutrients and pronounced core families of Hyphomicrobiaceae , Cytophagaceae , Pirellulaceae , Microbacteriaceae , and Phyllobacteriaceae were observed in our study ( Figure 3 A and Figure 5 ), suggesting the enhanced carbon and nitrogen biogeochemical processes in soils after sewage sludge usage, as these families have been widely reported to be capable of participating in relevant functions [ 109 , 110 , 111 , 112 ]. Together, these outcomes suggested that sewage sludge significantly improved the diversity of the bacterial community and functionality mainly by ameliorating microhabitats in coastal mudflat soil, which harbored alleviated saline–alkali conditions and promoted available nutrients.…”
Section: Discussionsupporting
confidence: 58%
“…demonstrated that the surrounding soils of corroded pipelines without petroleum contamination contained significantly more abundant Balneolaceae members ( Balneola and KSA1) [17]. The 16S rRNA gene amplicon-based metagenomic analysis revealed that Balneolaceae and some other bacterial groups were enriched differentially in the rhizosphere of Avicennia marina [18]. In this study, we report a novel moderately halophilic bacterium affiliated with Balneolaceae and establish its taxonomic position by using polyphasic approaches.…”
Section: Introductionmentioning
confidence: 88%
“…Bacterial wilt disease in Cucurbita maxima in China caused by Ralstonia solanacearum was identified using 16S rRNA gene sequencing of the isolates collected from the plants infected by wilt disease [ 33 ]. A recent study with 16S rRNA gene amplicon metagenomic analysis resulted in the identification of a rhizospheric microbial community of plants like Eichhornia crassipes [ 34 ] and mangrove species ( Sonneratia alba, Rhizophora mucronata, Ceriops tagal , and Avicennia marina ) [ 35 ].…”
Section: Road Map To Metagenomics Studymentioning
confidence: 99%